The investigated microstructure and mechanical properties of Al 2O3/20wt% TiO2 nanocomposite coating - Dejang N. (2014)
The incorporation of nano-size TiO2 particles can significantly enhance the microstructure and mechanic properties of Al2O 3 coating. Phase transformation from mainly stable α-Al 2O3 and anatase-TiO2 in the powders to predominant metastable γ-Al2O3 and rutile-TiO 2 in the coatings was observed. Reaction between Al2O 3 and TiO2 phase also occurred producing new phase Al 2TiO5 phase. Microstructural investigation showed that well separated TiO2 lamellas were homogeneously dispersed between Al2O3 lamellas. It was found that the plasma-sprayed composite coating possessed better wear resistance than that of monolithic Al2O3 coating. The addition of TiO2 was found to improve friction coefficient, wear resistance and fracture toughness.